2017
DOI: 10.4067/s0718-34292017005000019
|View full text |Cite
|
Sign up to set email alerts
|

Plantas hospedantes de Bemisia tabaci (Gennadius) (Hemíptera: Aleyrodidae), en áreas colindantes al cultivo de tomate, en la región este de Panamá

Abstract: Plantas hospedantes de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…From the second instar onwards, it loses mobility, and on the fourth, it stops feeding. It is a widely distributed pest, and it is reported that it attacks more than 500 host plants worldwide, including numerous weeds, vegetables, staples, oilseeds, fruit trees, and ornamentals [7]. To cause direct damage, nymphs, and adults feed by sucking the sap from the leaf.…”
Section: Bemicia Spmentioning
confidence: 99%
“…From the second instar onwards, it loses mobility, and on the fourth, it stops feeding. It is a widely distributed pest, and it is reported that it attacks more than 500 host plants worldwide, including numerous weeds, vegetables, staples, oilseeds, fruit trees, and ornamentals [7]. To cause direct damage, nymphs, and adults feed by sucking the sap from the leaf.…”
Section: Bemicia Spmentioning
confidence: 99%
“…En un estudio previo, nuestros resultados indicaron que las arvenses asociadas al cultivo de tomate son reservorios de begomovirus, tanto en época de cultivo como de barbecho. Las arvenses identificadas fueron: A. dubius, A. spinosus, C. mucunoides, C. (Zachrisson, Herrera y Bernal, 2017). Aunque las arvenses, pueden actuar como hospederos de plagas y patógenos, se conoce su efecto de dilución de las patogénesis, y su contribución a la sanidad de los cultivos (Bezerra, De Oliveira y Vasconcelos, 2004).…”
Section: Hospederos De Plagas Y Sus Controladores Biológicosunclassified